The effect of cold water immersion on arm muscle strength in the basketball teamThe effect of cold water immersion on arm muscle strength in the basketball team - Rizki Ramadhan; Prisca Widiawati; Muhammad Putra Ramadhan (Physical Education Departement of University PGRI Jombang, 2025)
The goal of this study is to determine the effect of cold water immersion on the arm muscle strength of the basketball team at SMA Negeri 3 of Malang City. This research utilizes an experimental study method. The design used in this research is the